2020
DOI: 10.3390/rs12183070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Temporal Variations of Orthometric/Normal Heights Induced by Hydrological Mass Variations over Large River Basins Using GRACE Mission Data

Abstract: Almost half of the Earth’s land is covered by large river basins. Temporal variations of hydrological masses induce time-varying gravitational potential and temporal mass loading that deforms the Earth’s surface. These phenomena cause temporal variations of geoid/quasigeoid and ellipsoidal heights that result in temporal variations of orthometric/normal heights ΔH/ΔH*. The aim of this research is to assess ΔH/ΔH* induced by hydrological masses over large river basins using the Gravity Recovery and Climate Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For the river basin of a weak hydrological signal, such as the Orange river basin, Δ𝐻/Δ𝐻 * do not exceed ±1 cm, while Δ𝐻/Δ𝐻 * can reach 8 cm in the case of the river basin of strong hydrological signal, e.g. the Amazon river basin (Godah et al, 2020c). The analyses of Δ𝐻/Δ𝐻 * obtained indicated that due to spatio-temporal patterns such as unusual floods, extreme drought, and rainfall seasonality within the entire river basin as well as the location of the upstream and downstream areas of the river basin, clear differences (e.g.…”
Section: Temporal Variations Of the Gravity Field From Grace/grace-fo...mentioning
confidence: 98%
See 2 more Smart Citations
“…For the river basin of a weak hydrological signal, such as the Orange river basin, Δ𝐻/Δ𝐻 * do not exceed ±1 cm, while Δ𝐻/Δ𝐻 * can reach 8 cm in the case of the river basin of strong hydrological signal, e.g. the Amazon river basin (Godah et al, 2020c). The analyses of Δ𝐻/Δ𝐻 * obtained indicated that due to spatio-temporal patterns such as unusual floods, extreme drought, and rainfall seasonality within the entire river basin as well as the location of the upstream and downstream areas of the river basin, clear differences (e.g.…”
Section: Temporal Variations Of the Gravity Field From Grace/grace-fo...mentioning
confidence: 98%
“…The analyses of Δ𝐻/Δ𝐻 * obtained indicated that due to spatio-temporal patterns such as unusual floods, extreme drought, and rainfall seasonality within the entire river basin as well as the location of the upstream and downstream areas of the river basin, clear differences (e.g. ±2 cm in the Amazon river basin) for Δ𝐻/Δ𝐻 * can be found within subareas of the same river basin (Godah et al, 2020c). For the area of Turkey, the differences between Δ𝐻/Δ𝐻 * in the same area at different epochs reach up to 25 mm, while those differences at the same epoch and different areas reach up to 9 mm (Öztürk et al, 2020).…”
Section: Temporal Variations Of the Gravity Field From Grace/grace-fo...mentioning
confidence: 99%
See 1 more Smart Citation